2022
DOI: 10.1039/d2ta01549h
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Zn anode surface chemistry for dendrite-free Zn ion batteries

Abstract: The zinc-ophobic tetramethylammonium sulfate electrolyte additive and zinc-ophilic ZnO@Cu artificial layer are used to inhibit Zn corrosion and dendrite growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…[ 40,41 ] From scanning electron microscopy (SEM) images of CuHCF nanoparticles, it can be found that the CuHCF particle size is uniform, and the nanospheres do not exceed 100 nm (Figure S2, Supporting Information). In addition, the specific surface area of 743.4 m 2 g ‐1 and the existence of mesopore pore size of CuHCF particles are confirmed by N 2 adsorption–desorption isotherms, which are beneficial to provide more zinc adsorption sites and form zinc ion transport channels to uniform zinc ion flux [ 34,42,43 ] The surface SEM images of bare Zn and Zn@CuHCF anode before cycling are exhibited in Figure S4 (Supporting Information), it can be found that the surface of bare Zn anode is not completely smooth and flat before cycling, and the coating layer surface is compact and dense. The water contact angle (WCA) test of the Zn@CuHCF and bare Zn electrode is compared under the same condition (Figure S5, Supporting Information), the WCA of the bare Zn surface is 75.0°, which is much higher than the 23.9° of Zn@CuHCF.…”
Section: Resultsmentioning
confidence: 99%
“…[ 40,41 ] From scanning electron microscopy (SEM) images of CuHCF nanoparticles, it can be found that the CuHCF particle size is uniform, and the nanospheres do not exceed 100 nm (Figure S2, Supporting Information). In addition, the specific surface area of 743.4 m 2 g ‐1 and the existence of mesopore pore size of CuHCF particles are confirmed by N 2 adsorption–desorption isotherms, which are beneficial to provide more zinc adsorption sites and form zinc ion transport channels to uniform zinc ion flux [ 34,42,43 ] The surface SEM images of bare Zn and Zn@CuHCF anode before cycling are exhibited in Figure S4 (Supporting Information), it can be found that the surface of bare Zn anode is not completely smooth and flat before cycling, and the coating layer surface is compact and dense. The water contact angle (WCA) test of the Zn@CuHCF and bare Zn electrode is compared under the same condition (Figure S5, Supporting Information), the WCA of the bare Zn surface is 75.0°, which is much higher than the 23.9° of Zn@CuHCF.…”
Section: Resultsmentioning
confidence: 99%
“…4j). 47,48 As investigated by molecular dynamics (MD) simulations (Fig. S9, ESI†), the ZnSO 4 + ZnI 2 /H 2 O + EG solution shows an altered Zn 2+ solvation structure compared to the ZnI 2 + ZnSO 4 /H 2 O solution because the coordinated H 2 O molecules are partially replaced by EG.…”
Section: Resultsmentioning
confidence: 99%
“…4j). 47,48 As investigated by molecular dynamics (MD) simulations (Fig. S9 The resultant [Zn(H 2 O) 5 EG] 2+ has lower electrostatic potential and larger size compared to the [Zn(H 2 O) 6 ] 2+ , which could inhibit the heterogeneous 2D Zn 2+ diffusion associated with dendrite formation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the substantial polar groups, the polymer coating has highly zincophilicity, which promotes Zn 2 + flux, directs uniform redistribution of Zn 2 + , and inhibits the growth of dendrite. Xu et al [67] built dense and uniform ZnO@Cu protected interfacial layer with highly zincophilicity by TS electrolyte additive on the zinc anode (Figure 5b), which enhances the electrochemical stability of the zinc anode and insulates the anode from the electrolyte to prevent hydrogen evolution. Furthermore, the zincophilic ZnO@Cu interfacial layer can provide zinc ion nucleation sites, greatly inhibit the formation of zinc dendrites, and improve the electrochemical performance of zinc anode.…”
Section: In Situ Reaction To Form Zincophilic Seimentioning
confidence: 99%